Rocker Bogie Mechanism for Military Application - Suraj Magar,; A.S.Shirkande,; Pranav Patil,; Prathmesh Lokhande, (Journal of Electronic Design Engineering, 2023)
The exploration of space has been one of the greatest endeavours of humankind in the last few decades. The success of missions to Mars and the Moon has been largely attributed to the use of rovers equipped with the rocker-bogie mechanism. This system has proven to be a reliable and robust mechanism that enables the rover to traverse uneven terrain and avoid rollovers, which can be dangerous for both the rover and its payload. However, one disadvantage of the current systems is that their speed is slow. This limits the distance they can cover. To address this issue, a new suspension mechanism has been designed that builds upon the strengths of the rocker-bogie system while addressing its limitations. This means that rovers can travel faster while maintaining the same level of safety. The project aims to improve the basic workings of the rocker-bogie mechanism so that it can perform better. One of the ways this can be achieved is by altering the control strategy without requiring any adjustments to the current design. This can be done by implementing more advanced algorithms for obstacle avoidance, navigation, and communication. However, to realize the full potential benefits of the new suspension mechanism and significantly enhance the practical operational velocity of upcoming rovers, certain mechanical modifications have been proposed. These modifications include changes to the size and shape of the wheels and the suspension system, as well as the addition of new sensors and actuators.